Comparative effects of six-minute treadmill walk and six-minute treadmill walk-talk test on the cardiopulmonary parameters of healthy individuals - Chidozie Mbada; Oladayo Jide Adeagbo; Jibril Mohammed; Bashir Kaka; Aisha Shittu; Farida Sumaila; Adewale Oyewole; Moses Makinde (Shiraz University of Medical Sciences, 2021)
Objective: To compare the effect of Six-Minute Treadmill Walk Test (6MTWT) and Six-Minute Treadmill Walk-Talk Test (6MTWTT) on cardiopulmonary parameters. Methods: A total of 35 Nigerian undergraduate students with stable cardiopulmonary parameters at baseline were recruited into this pre-test - post-test experimental study using convenient sampling. The participants performed a 6MTWT and 6MTWTT (after two hours interval between tests) on a powered treadmill using standard protocol. Systolic and diastolic blood pressures (SBP and DBP), heart rate (HR), rate pressure product (RPP), metabolic equivalents (METs), saturated partial pressure of oxygen (SPO2) and the rate of perceived exertion (RPE)were measured.   Results: The results showed that both the 6MTWT and 6MTWTT lead to significant increases in the values of SBP, HR, METs, RPE and RPP (p <0.05), except for DBP where the change was not significant (p>0.05). Comparatively,  post walk tests results revealed there was significantly higher RPE and SPO2 scores with 6MTWT compared to 6MTWTT (p <0.05), while other parameters were comparable (p <0.05). Furthermore, SBP, PR and RPP of both tests correlated moderately with each other (p <0.05). Conclusion: 6MTWT and 6MTWTT, similarly evoke cardiopulmonary changes among apparently healthy young individuals. However, 6MTWTT led to less oxygen consumption and myocardial oxygen demand compared with 6MTWT. This finding may be potentially beneficial for future cardiopulmonary exercise testing using 6MWT.